Algorithm 757 MISCFUN, a software package to compute uncommon special functions. - MacLeod, Allan J.
MISCFUN (MISCellaneous FUNctions) is a Fortran package for the evaluation of several special functions, which are not used often enough to have been included in the standard libraries or packages. The package uses Chebyshev expansions as the underlying method of approximation, with the Chebyshev coefficients given to 20D. A wide variety of functions are included, and the package is designed so that other functions can be added in a standard manner.
Keywords: Chebyshev polynomials; Special functions